1978
DOI: 10.1111/j.1365-2125.1978.tb00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of piretanide, bumetanide and frusemide on electrolyte and urate excretion in normal subjects.

Abstract: 1The pharmacological actions of a new short acting loop diuretic were investigated in nine healthy male subjects and compared with those of frusemide and bumetanide. Subjects received 6 mg piretanide/day, 40 mg frusemide/day or 1 mg bumetanide/day for a period of 1 week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
29
5

Year Published

1979
1979
1994
1994

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 14 publications
(11 reference statements)
7
29
5
Order By: Relevance
“…Recent previous studies in rat and in man showed piretanide to be more potent than frusemide (Merkel et al 1976;Roberts, Homeida, Roberts & Bogie, 1978). Given orally in man, 6 mg piretanide were found to be equivalent to 40 mg frusemide and less efficacious than 1 mg bumetanide (Roberts et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Recent previous studies in rat and in man showed piretanide to be more potent than frusemide (Merkel et al 1976;Roberts, Homeida, Roberts & Bogie, 1978). Given orally in man, 6 mg piretanide were found to be equivalent to 40 mg frusemide and less efficacious than 1 mg bumetanide (Roberts et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Lysin acetylsalicylate, when given before the diuretics, significantly decreased the diuresis and sodium excretion, and appeared to increase potassium excretion, when given before frusemide but not before piretanide. Lawrence et al (1978) and Roberts et al (1978) have shown, in healthy volunteers, that piretanide has a diuretic effect similar to that of frusemide; one of our previous studies (Valette et al, 1979) de-monstrated that frusemide and piretanide significantly increase venous compliance. Lysin acetylsalicylate inhibits diuresis and the effect on venous compliance when given before both diuretics.…”
Section: Interaction Between Salicylate and Two Loop Diureticsmentioning
confidence: 99%
“…Many studies have shown a direct effect of frusemide on renal prostaglandin metabolism (Bailie, Crosslan & Hook, 1976;Williamson, Bourland & Marchand, 1975). Piretanide, a new high ceiling diuretic, seems to have a similar action to that of frusemide (Merkel, Bormann, Mania, Muschaweck & Hropot, 1976;Lawrence, Ansari & Elliot, 1978;Roberts, Homeida, Roberts & Bogie, 1978;Valette, Duhaze & Apoil, 1979). This study was undertaken to investigate a possible interaction between diuretics and lysin acetylsalicylate, with particular reference to water and sodium excretion, and venous compliance.…”
Section: Interaction Between Salicylate and Two Loop Diureticsmentioning
confidence: 99%
“…An increase in uric acid excretion immediately following diuretic administration and subsequent retention of uric acid favoured the latter, and suggested that homeostatic sodium-conserving mechanisms might be responsible (Roberts, Homeida, Roberts & Bogie, 1978) Such mechanisms are known to affect the relationship between plasma frusemide level and sodium excretion rate as diuresis proceeds (Branch, Roberts, Homeida & Levine, 1977).…”
mentioning
confidence: 99%